Antimicrobial susceptibility monitoring of canine and feline skin and ear pathogens isolated from European veterinary clinics: results of the ComPath Surveillance programme. Issue 6 (13th September 2020) - de Jong, Anno; Youala, Myriam; El Garch, Farid; Simjee, Shabbir; Rose, Markus; Morrissey, Ian; Moyaert, Hilde
Abstract : Background: The ComPath project is a pan‐European programme dedicated to the monitoring of antimicrobial susceptibility of canine and feline pathogens using standardized methods and centralized minimal inhibitory concentration (MIC) determination. Objectives: To report antimicrobial susceptibilities of major pathogens isolated from nontreated animals with acute clinical signs of skin, wound or ear infections in 2013–2014. Methods and materials: MICs were determined by agar dilution for commonly used drugs and interpreted using Clinical and Laboratory Standards Institute (CLSI) breakpoints, if available. Results: Of 1, 676 isolates recovered, the main species isolated from dogs were Staphylococcus pseudintermedius, followed by Streptococcus spp., Pseudomonas aeruginosa and Escherichia coli . In cats, Pasteurella multocida, coagulase‐negative staphylococci (CoNS) and Staphylococcus aureus were isolated most frequently. Resistance rates observed for S. pseudintermedius were <26.7% for penicillin, clindamycin and chloramphenicol, and ≤11.5% for ampicillin, amoxicillin/clavulanate, cefalexin, cefovecin, gentamicin and fluoroquinolones. For S. aureus, resistance rates ranged up to 90.9% for β‐lactams, and were 19.7% for clindamycin, 27% for fluoroquinolones and 0.0–6.1% for other drugs. The mecA gene was confirmed by PCR in 10.6% of S. pseudintermedius, 11.6% of CoNS and 31.4% of S. aureus isolates. In streptococci/enterococci, resistance to penicillin, ampicillin and chloramphenicol ranged from 0.0% to 11.3%, whereas fluoroquinolone resistance ranged from 0.0% to 8.5%. For E. coli, resistance ranged from 13.8 to 15.9% for fluoroquinolones and from 86.2% to 100.0% for β‐lactams. Low rates of resistance (0.0–6.3%) were observed in P. multocida, and for P. aeruginosa resistance to gentamicin was 10.3%. Conclusion: Overall, antimicrobial resistance of cutaneous/otic pathogens isolated from dogs and cats was low (1–10%) to moderate (10–20%). For several pathogens, the paucity of CLSI recommended breakpoints for veterinary use is a bottleneck. Abstract : Background – The ComPath project is a pan‐European programme dedicated to the monitoring of antimicrobial susceptibility of canine and feline pathogens using standardized methods and centralized minimal inhibitory concentration (MIC) determination. Objectives – To report antimicrobial susceptibilities of major pathogens isolated from nontreated animals with acute clinical signs of skin, wound or ear infections in 2013–2014. Conclusion – Overall, antimicrobial resistance of cutaneous/otic pathogens isolated from dogs and cats was low (1–10%) to moderate (10–20%). For several pathogens, the paucity of CLSI recommended breakpoints for veterinary use is a bottleneck. Résumé: Contexte: Le projet ComPath est un programme européen dédié à la surveillance de la sensibilité des pathogènes aux anti‐microbiens du chien et du chat à l'aide de méthodes standardisées et centralisées de détermination de concentration minimale inhibitrice (MIC). Objectifs: Décrire les sensibilités anti‐microbiennes de la plupart des pathogènes isolés d'animaux non traités avec des signes cliniques d'infections cutanées, auriculaires ou de plaies en 2013‐2014. Matériels et méthodes: Les MICs ont été déterminées par dilution sur agar pour la plupart des molécules fréquemment utilisées et interprétés par CLSI (Clinical and Laboratory Standards Institute) si disponible. Résultats: Sur les 1676 souches obtenues, la principale espèce isolée chez le chien était Staphylococcus pseudintermedius, suivie de Streptococcus spp., Pseudomonas aeruginosa et Escherichia coli . Chez le chat, Pasteurella multocida, staphylocoque coagulase‐négative (CoNS) et Staphylococcus aureus étaient isolés les plus fréquemment. Les taux de résistance observés pour S. pseudintermedius étaient <26.7% pour la pénicilline, la clindamycine et le chloramphénicol, et ≤11.5% pour l'ampicilline, l'amoxicilline/acide clavulanique, la céphalexine, la céfovécine, la gentamicine et les fluoroquinolones. Pour S. aureus, les taux de résistance allaient jusqu'à 90.9% pour les β‐lactames, et étaient 19.7% pour la clindamycine, 27% pour les fluoroquinolones et 0.0–6.1% pour les autres molécules. Le gène mecA était confirmé par PCR pour 10.6% des S. pseudintermedius, 11.6% des CoNS et 31.4% des S. aureus . Pour streptococci/enterococci, la résistance à la pénicilline, ampicilline et chloramphénicol allait de 0.0% à 11.3%, tandis que la résistance aux fluoroquinolones allait de 0.0% to 8.5%. Pour E. coli, la résistance allait de 13.8 à 15.9% pour les fluoroquinolones et de 86.2% à 100.0% pour les b‐lactams. De faibles taux de résistance (0.0–6.3%) étaient observés pour P. multocida, et la résistance de P. aeruginosa à la gentamicine était de 10.3%. Conclusion: Ainsi, les résistances antimicrobiennes des pathogènes auriculaires/cutanés isolés de chiens et chats étaient faibles (1‐10%) à modéré (10‐20%). Pour plusieurs pathogènes, le manque de données recommandées de CLSI à usage vétérinaire est un facteur limitant. Resumen: Introducción: el proyecto ComPath es un programa paneuropeo dedicado al seguimiento de la susceptibilidad antimicrobiana de patógenos caninos y felinos mediante métodos estandarizados y determinación centralizada de concentración mínima inhibitoria (MIC). Objetivos: Informar sobre la susceptibilidad antimicrobiana de los principales patógenos aislados de animales no tratados con signos clínicos agudos de infecciones de la piel, heridas u oídos en 2013‐2014. Métodos y materiales: las MICs se determinaron mediante dilución en agar para los medicamentos de uso común y se interpretaron utilizando los puntos de corte del Instituto de estandardización clínica y laboratorial (CLSI), si estaban disponibles. Resultados: De los 1.676 aislados recuperados, las principales especies aisladas de perros fueron Staphylococcus pseudintermedius, seguidas de Streptococcus spp., Pseudomonas aeruginosa y Escherichia coli . En gatos, se aislaron con mayor frecuencia Pasteurella multocida, estafilococos coagulasa negativos (CoNS) y Staphylococcus aureus . Las tasas de resistencia observadas para S. pseudintermedius fueron <26, 7% para penicilina, clindamicina y cloranfenicol, y ≤ 11, 5% para ampicilina, amoxicilina/clavulánico, cefalexina, cefovecina, gentamicina y fluoroquinolonas. Para S. aureus, las tasas de resistencia variaron hasta el 90, 9% para los β‐lactámicos y fueron del 19, 7% para la clindamicina, del 27% para las fluoroquinolonas y del 0, 0 al 6, 1% para otros fármacos. El gen mecA fue confirmado por PCR en el 10, 6% de S. pseudintermedius, el 11, 6% de CoNS y el 31, 4% de los aislados de S. aureus . En estreptococos/enterococos, la resistencia a penicilina, ampicilina y cloranfenicol oscilaron entre el 0, 0% y el 11, 3%, mientras que la resistencia a las fluoroquinolonas varió entre el 0, 0% y el 8, 5%. Para E. coli, la resistencia varió del 13, 8 al 15, 9% para las fluoroquinolonas y del 86, 2% al 100, 0% para los b‐lactámicos. Se observaron tasas bajas de resistencia (0, 0‐6, 3%) en P. multocida, y para P. aeruginosa la resistencia a la gentamicina fue del 10, 3%. Zusammenfassung: Hintergrund: Das CompPath Projekt ist ein pan‐europäisches Programm, welches der Überwachung der antimikrobiellen Empfindlichkeit von caninen und felinen Pathogenen mittels standardisierter Methoden und zentraler Bestimmung einer minimalen inhibitorischen Konzentration (MIC) dient. Ziele: Der Beschreibung antimikrobieller Empfindlichkeiten von wichtigen Pathogenen, die von unbehandelten Tieren mit akuten klinischen Anzeichen auf der Haut, mit Wund‐ oder Ohrinfektionen in den Jahren 2013‐2014 isoliert wurden. Methoden und Materialien: MICs wurden mittels Agardilution für häufig verwendete Medikamente bestimmt und mithilfe der Clinical and Laboratory Standards Institute (CLSI) Breakpoints falls vorhanden, interpretiert. Ergebnisse: Von den 1676 gewonnenen Isolaten handelte es sich bei der hauptsächlich isolierten Spezies von Hunden um Staphylococcus pseudintermedius, gefolgt von Streptococcus spp., Pseudomonas aeruginosa und Escherichia coli . Bei Katzen wurden am häufigsten Pasteurella multocida, Koagulase‐negative Staphylokokken (CoNS) und Staphylococcus aureus isoliert. Die Resistenzraten für S. pseudintermedius waren <26, 7% für Penicillin, Clindamycin und Chloramphenicol, und ≤11, 5% für Ampicillin, Amoxicillin/Clavulansäure, Cefalexin, Cefovecin, Gentamicin und Fluoroquinolone. Für S. aureus reichten die Resistenzwerte bis zu 90, 9% für β‐Laktame, lagen bei 19, 7% für Clindamycin, bei 27% für Fluoroquinolone und 0, 0‐6, 1% für andere Medikamente. Das mecA Gen wurde mittels PCR bei 10, 6% der S. pseudintermedius, bei 11, 6% der CoNS und bei 31, 4% der S. aureus Isolate bestätigt. Bei Streptokokken/Enterokokken reichte die Resistenz auf Penicillin, Ampicillin und Chloramphenicol von 0, 0% bis 11, 3%, während die Fluoroquinolon Resistenz zwischen 0, 0% und 8, 5% lag. Bei E.coli reichte die Resistenz auf Fluoroquinolone von 13, 8 bis 15, 9% und auf β‐Laktame von 86, 2% bis 100, 0%. Es wurden niedrige Resistenzraten (0, 0‐6, 3%) bei P. multocida beobachtet und die Resistenz von P. aeruginosa auf Gentamicin lag bei 10, 3%. Schlussfolgerung: Insgesamt war die antimikrobielle Resistenz von kutanen/otischen Pathogenen, die von Hunden und Katzen isoliert worden waren, niedrig (1‐10%) bis moderat (10‐20%). Für mehrere Pathogene macht es der Mangel an CLSI schwierig Breakpoints zur tierärztlichen Verwendung zu empfehlen. 要約: 背景: ComPathプロジェクトは、標準法及び集中型最小発育阻止濃度（MIC）決定を用いた、犬及び猫の病原菌の抗菌薬感受性モニタリングに特化した汎ヨーロッパプログラムである。 目的: 本研究の目的は、2013〜2014年に皮膚、創傷、または耳感染症の急性臨床兆候を示した未治療動物から分離された、主要な病原体の抗菌薬感受性を報告することであった。 材料と方法: MIC値は、一般的に使用される薬物に対し、寒天希釈で決定し、可能であれば、Clinical and Laboratory Standards Institute（CLSI）ブレークポイントを使用して解釈した。 結果: 分離された1, 676株のうち、犬から分離された主な種は Staphylococcus pseudintermedius で、続いてストレプトコッカス属、緑膿菌、および大腸菌であった。猫では、 Pasteurella multocida 、コアグラーゼ陰性ブドウ球菌（CoNS）、 S. aureus が最も頻繁に分離された。 S. pseudintermedius で観察された耐性率は、ペニシリン、クリンダマイシン、クロラムフェニコールで26.7％未満、アンピシリン、アモキシシリン/クラブラン酸、セファレキシン、セフォベシン、ゲンタマイシン、フルオロキノロンで11.5％以下であった。 S. aureus の耐性率は、β‐ラクタム系抗菌薬で最大90.9％、クリンダマイシンで19.7％、フルオロキノロンで27％、その他の薬物で0.0〜6.1％であった。 mecA 遺伝子はPCR法により、 S. pseudintermedius の10.6％、CoNSの11.6％、および S. aureus の分離株の31.4％に確認された。連鎖球菌/腸球菌では、ペニシリン、アンピシリン及びクロラムフェニコールに対する耐性は0.0％から11.3％の範囲であったが、フルオロキノロン耐性は0.0％から8.5％の範囲であった。大腸菌における耐性は、フルオロキノロンで13.8〜15.9％、β‐ラクタム系抗菌薬で86.2％〜100.0％の範囲であった。 P. multocida で低い耐性率（0.0–6.3％）が観察され、緑膿菌のゲンタマイシン耐性は10.3％であった。 結論: 全体として、犬及び猫から分離された皮膚/耳の病原体の抗菌薬耐性は低く（1〜10％）中程度（10〜20％）であった。いくつかの病原体にとって、獣医用のCLSI推奨ブレークポイント不足がボトルネックである。 摘要: 背景: ComPath是一个泛欧洲项目，致力于使用标准化方法和集中测定最小抑菌浓度(MIC)，监测犬和猫病原体的抗菌药物敏感性。 目的: 2013‐2014年从有皮肤、伤口或耳部急性感染症状，但未治疗的动物身上分离主要病原体，报告其抗菌药物敏感性。 方法和材料: 通过琼脂稀释法测定常用药物的MIC，并使用临床和实验室标准协会(CLSI)断点（如有的话）进行判读。 结果: 在收集的1676个分离菌株中，犬的主要菌种为假中间型葡萄球菌，其次为链球菌属、铜绿假单胞菌和大肠埃希菌。在猫身上，多杀巴氏杆菌、凝固酶阴性葡萄球菌(CoNS)和金黄色葡萄球菌的分离频率最高。观察耐药率，对于假中间型链球菌，青霉素、克林霉素和氯霉素的耐药率<26.7%，对氨苄西林、阿莫西林/克拉维酸、头孢氨苄、头孢维星、庆大霉素和氟喹诺酮类的耐药率≤11.5%。对于金黄色葡萄球菌，β‐内酰胺类的耐药率高达90.9%，克林霉素的耐药率为19.7%，氟喹诺酮类的耐药率为27%，其他药物的耐药率为0.0‐6.1%。10.6%的假中间型链球菌、11.6%的CoNS和31.4%的金黄色葡萄球菌分离株经PCR证实存在mecA基因。对于链球菌/肠球菌，青霉素、氨苄西林和氯霉素的耐药性范围为0.0%‐11.3%，而氟喹诺酮类的耐药性范围为0.0%‐8.5%。对于大肠埃希菌，氟喹诺酮类的耐药率范围为13.8%‐15.9%，β‐内酰胺类的耐药率范围为86.2%‐100.0%。我们发现多杀巴氏杆菌的耐药率较低(0.0‐6.3%)，对于铜绿假单胞菌，庆大霉素的耐药率为10.3%。 结论: 总体而言，从犬和猫身上分离的皮肤/耳道病原体的抗菌耐药性为低(1‐10%)至中度(10‐20%)。对于几种病原体，缺乏CLSI推荐的兽医用断点是一个瓶颈。 Resumo: Contexto: O projeto ComPath é um programa pan‐europeu dedicado ao monitoramento da susceptibilidade a antimicrobianos de patógenos caninos e felinos utilizando métodos padronizados e determinação centralizada da concentração inibitória mínima (MIC). Objetivos: Relatar as suscetibilidades a antimicrobianos dos principais patógenos isolados de animais não tratados apresentando sinais clínicos agudos de pele, feridas ou infecções de ouvido no período de 2013–2014. Métodos e materiais: Os MICs foram determinados por diluição em ágar para fármacos comumente utilizados e interpretados usando pontos de corte do Clinical and Laboratory Standards Institute (CLSI), se disponíveis. Resultados: Dos 1.676 isolados recuperados, as principais espécies isoladas de cães foram Staphylococcus pseudintermedius, seguido por Streptococcus spp., Pseudomonas aeruginosa e Escherichia coli. Em gatos, Pasteurella multocida, estafilococos coagulase‐negativos (CoNS) e Staphylococcus aureus foram isolados com mais frequência. As taxas de resistência observadas para S. pseudintermedius foram <26, 7% para penicilina, clindamicina e cloranfenicol e ≤11, 5% para ampicilina, amoxicilina/clavulanato, cefalexina, cefovecina, gentamicina e fluoroquinolonas. Para S. aureus, as taxas de resistência variaram até 90, 9% para β‐lactâmicos e foram 19, 7% para clindamicina, 27% para fluoroquinolonas e 0, 0‐6, 1% para outros medicamentos. O gene mecA foi confirmado por PCR em 10, 6% dos isolados de S. pseudintermedius, 11, 6% dos CoNS e 31, 4% dos isolados de S. aureus. Em estreptococos / enterococos, resistência à penicilina, à ampicilina e ao cloranfenicol variaram de 0, 0% a 11, 3%, enquanto a resistência às fluoroquinolonas variou de 0, 0% a 8, 5%. Para E. coli, a resistência variou de 13, 8 a 15, 9% para fluoroquinolonas e de 86, 2% a 100, 0% para b‐lactâmicos. Baixas taxas de resistência (0, 0–6, 3%) foram observadas em P. multocida, e para P. aeruginosa a resistência à gentamicina foi de 10, 3%. Conclusão: No geral, a resistência a antimicrobianos de patógenos cutâneos/óticos isolados de cães e gatos foi baixa (1–10%) a moderada (10–20%). Para vários patógenos, a escassez de pontos de corte recomendados pelo CLSI para uso veterinário é um gargalo.